The lesser evil? Public opinion towards regulating fake news in three Asian countries - John W. Cheng; Hitoshi Mitomo; Youngkyoung Seo; Artima Kamplean (International Telecommunications Society (ITS), 2020)
This study empirically examines factors that influence public opinion towards regulating fake news in three Asian countries: Japan, South Korea, and Thailand. Based on the lesser evil principle, it is hypothesised that the perceived harm of fake news (one evil) will increase one's support towards regulating it. In parallel, it is also anticipated that some people might realise that restricting fake news may also harm freedom of expression (another evil) and thus, those who use fact-checking websites (a non-regulatory counter fake news solution) would be less supportive towards regulating fake news. Using original survey data collected from the three countries (n=5,218) and multi-group SEM analysis, it is found that the above hypotheses hold true for respondents from Japan and South Korea, but not for those from Thailand. This implies that the lesser evil principle may be applicable only in democratic countries, where freedom of expression is protected.
Keywords: 330